A-pore conexión sensitiva (2022)
The disconnection between the patrimonial context with the urban one generates different problems at an architectural, social and cultural level, over time heritage must prevail in accordance with its environment since it represents history, culture and tradition, through readjustment It is intended that the ruins of Pore Casanare, which are the Jesuit church and the prison, both from the time of the Spanish viceroyalty and the liberating route, this readjustment is for the purpose of preserving and conserving them by maintaining some uses as equipment. but demolish uses that may affect in the future such as housing and commerce in this readjustment controlled uses are managed always maintaining a hierarchy which is the ruins, it is connected to urban landmarks through the pore park Santander is affected by abandonment and not having attractiveness in front of the community so they can connect to their urban surroundings in a more appropriate way and with the same language, in each of these tas the project is presented in 3 epiphany structures, pore Santander park and Ramón nonato Pérez cultural house always with a social and cultural objective of understanding and showing not only physical but intangible heritage such as traditions and their history are proposed through of an audiovisual narrative and an architecture paramented to its environment